2015
DOI: 10.1007/978-3-319-20346-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Titania Nanotubes for Local Drug Delivery from Implant Surfaces

Abstract: The principal challenge for bone therapy is to deliver an effective dose of therapeutic agent (for example antibiotic or anti-cancer drug) to the affected site within bone, while sparing other organs. The solution to this dilemma is to deliver drug locally within the bone; hence various surface/therapeutic modifications of the conventional bone implants have been suggested to achieve this. Implants composed of biocompatible materials and loaded with active therapeutics thus provide one possible option for effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 160 publications
(239 reference statements)
0
18
0
Order By: Relevance
“…Titania Nanotubes 2.1.1. Fabrication Optimization Titania (TiO 2 ) nanotubes (TNTs) can be fabricated on Ti or its alloys via electrochemical anodization (EA) [35]. Briefly, EA involves the immersion of a Ti implant as an anode and a bare Ti/Pt electrode (cathode) inside an electrolyte (containing fluoride and water), with the supply of adequate current/voltage [31].…”
Section: Nanoscale Dental Implant Modificationsmentioning
confidence: 99%
“…Titania Nanotubes 2.1.1. Fabrication Optimization Titania (TiO 2 ) nanotubes (TNTs) can be fabricated on Ti or its alloys via electrochemical anodization (EA) [35]. Briefly, EA involves the immersion of a Ti implant as an anode and a bare Ti/Pt electrode (cathode) inside an electrolyte (containing fluoride and water), with the supply of adequate current/voltage [31].…”
Section: Nanoscale Dental Implant Modificationsmentioning
confidence: 99%
“…We have previously discussed the advantages of anodic TiO 2 nanotubes on osteoinduction and osteogenesis and their validity for a wide range of Ti alloy substrates. The nanotubes’ high surface area and their distinct topography can provide their full advantage in drug/active agents delivery applications [ 14 , 227 , 228 ]. Extensive studies are investigating the release profiles of drugs, including antibiotics, peptides, metal ions (Ag, zinc - Zn, copper - Cu), or various biopolymer coatings.…”
Section: Tailoring Osteoinduction With Anodic Tio 2 Nanotubesmentioning
confidence: 99%
“…Considering that chronic implant-associated bone infections represent a major problem in orthopedic and trauma-related surgery due to the severe complications in the affected patients, increasing interest has been given to design surfaces with bacteriostatic and bactericidal properties. With this purpose, many antibacterial agents such as antibiotics, metal ions, anti-microbial peptides, and biopolymer coatings [14,227,295,296] were incorporated into TiO 2 NTs and investigated for their therapeutic efficiency, mostly by in vitro antibacterial and cell culture-based studies. A very recent paper by Wu et al [278] has revealed the antibacterial potential of polyhexamethylene guanidine (PHMG) coated TiO 2 NTs (PHMG-NTs) in an animal model implanted with Staphylococcus aureus-contaminated rods in the femoral medullary cavity.…”
Section: In Vivo Drug Delivery Approaches Using Anodic Tio 2 Nanotube Implantsmentioning
confidence: 99%
“…Various strategies have been employed for nano-engineering Zr implants, such as electrochemical anodization (EA) [ 17 ], plasma treatment [ 18 ], micro-arc oxidation [ 19 ], hydrothermal treatment [ 20 ], chemical co-precipitation, and sol–gel method [ 21 ]. Among these, EA stands out due to its cost-effectiveness, scalability, and control over the characteristics of the fabricated nanostructures [ 22 ]. Briefly, EA involves immersion of a target substrate (Zr) as an anode and a counter electrode (cathode) in a suitable electrolyte (containing water and fluoride ions), and a supply of constant voltage/current.…”
Section: Introductionmentioning
confidence: 99%